An Unusual Case of Septic Arthritis of the Hip - UJJWAYINI RAY; SOMA DUTTA; ARPITA SUTRADHAR (Journal of Clinical and Diagnostic Research, 2016)
Non-typhoidal Salmonella, particularly Salmonella enterica serovar typhimurium is food borne pathogen causing mild self-limiting diarrhoea in healthy adults. It can occasionally cause extraintestinal focal infection in susceptible patients. Salmonella, as the aetiological agent of osteomyelitis and septic arthritis is rare and has been mostly reported in patients with sickle cell disease or thalassaemia. We report a case of septic arthritis by Salmonella typhimurium in an immunocompromised patient who was successfully treated following timely isolation and identification of the aetiological agent.